Array Region Analyses by Abstract Interpretation Approaches - Lari, Ilaria; Ricci, Laura (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2000: Anais do XII Symposium on Computer Architecture and High Performance ComputingDO - 10.5753/sbac-pad.2000.41229, 2000)
This paper presents some static analysis to detect the portion of a data structure accessed in a region of the program, such as a loop nest. Each analysis returns a set of data access descriptors summarizing, through a set of approximations, the data accessed in the region. The analyses have been defined through an abstract interpretation framework. The paper reviews several previously defined abstract domains and shows that some of them are suitable for the analysis of interest. Then, a new domain is proposed and the interpretation is defined through a systematic approach to combine abstract interpretations. Using this approach, an analyzer has been automatically generated from the analysis specification. The application of the analyzer to union cases of interest is shown as well.